Chronic bronchitis – new clinical recommendations (main provisions): A review on behalf of the working group for the development and revision of clinical guidelines for chronic bronchitis - Igor V. Leshchenko; Sergey N. Avdeev; Andrey A. Zaytsev; Svetlana I. Ovcharenko (Терапевтический архив)
Chronic bronchitis (CB) is one of the most commonly diagnosed non-communicable chronic diseases. At the same time, with such a high incidence of CB registered in the Russian Federation, this pathology requires a balanced approach to the interpretation of clinical and functional indicators and their differentiated approach. The main provisions of the new clinical recommendations on CB, which are reflected in the article, will be useful in the practical work of an internist.